2002
DOI: 10.1161/01.hyp.0000026809.68674.f9
|View full text |Cite
|
Sign up to set email alerts
|

ET B Receptor in Renal Medulla Is Enhanced by Local Sodium During Low Salt Intake

Abstract: Abstract-Renal endothelin-1 participates in sodium and water handling, and its urinary excretion is increased in sodium-retentive states. We compared the cortical and medullary renal expression of prepro-endothelin-1, endothelinconverting enzyme-1, and endothelin type A and type B receptors in patients who underwent nephrectomy after normal (108 mmol/d NaCl; nϭ6) or low (20 mmol/d NaCl; nϭ6) sodium diet and investigated whether sodium exerts a direct role on endothelin receptor binding in vitro. With normal so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Currently, there are few studies examining the effects of dietary sodium on ETR expression, and the results appear to be somewhat inconsistent. Treating cell membrane from human renal medullary tissue in vitro with high sodium concentration increased the expression of ET B R but did not alter the ET A R expression (59). In DOCA saltsensitive hypertension, there is an increased ET B R binding in renal medulla (46).…”
Section: Dual Effects Of Et-1: Role Of Dietary Sodium Intakementioning
confidence: 87%
“…Currently, there are few studies examining the effects of dietary sodium on ETR expression, and the results appear to be somewhat inconsistent. Treating cell membrane from human renal medullary tissue in vitro with high sodium concentration increased the expression of ET B R but did not alter the ET A R expression (59). In DOCA saltsensitive hypertension, there is an increased ET B R binding in renal medulla (46).…”
Section: Dual Effects Of Et-1: Role Of Dietary Sodium Intakementioning
confidence: 87%
“…S2024, BachemPeninsula, San Carlos, Calif), as described previously. 9,[15][16][17] The minimum detectable ET-1 amount was 0.1 pg.…”
Section: Et-1 Assaymentioning
confidence: 91%
“…This indicates that ET‐1/ET B in the renal medulla CD controls salt sensitivity and blood pressure. Conversely, another group has shown that a low‐sodium diet (1.2 g/day) increased prepro‐ET‐1 and ET B receptor expression in the kidney of patients who had undergone nephrectomy 44,45 . The reason why the renal ET system would be upregulated in patients who should have augmented sodium reabsorption due to the low‐sodium diet is unclear, but because functional activity was not assessed in those studies we do not know whether this indicates a defect in the ET system of these patients, a disparity between humans and rodents or simply that mRNA or binding measurements are a poor reflection of functional activity.…”
Section: Endothelin‐1 and Its Receptors In The Kidneymentioning
confidence: 96%